The (un)making of marine park subjects: Environmentality and everyday resistance in a coastal Tanzanian village. (February 2020) - Raycraft, Justin
Highlights: This paper focuses on local resistance to a marine park in southeastern Tanzania. It reveals how and why villagers oppose the park. Some people protested against the park overtly by destroying its gatehouse office. A violent response from state paramilitary forces, and top-down enforcement, have instilled fear. Many people instead engage in subtle acts of noncompliance to conservation regulations. Abstract: This paper focuses on local conflicts over marine conservation in southeastern Tanzania. It draws from ethnographic fieldwork conducted in 2014 and 2015 in a coastal village located inside the boundaries of a marine park. The paper first examines why villagers have come to contest the park, and subsequently outlines the various forms of resistance they employ to mobilize their opposition. Some people are willing to protest openly, as evidenced by the destruction of the park's gatehouse office and directory signs in 2013. However, an immediate violent response to such acts from state paramilitary forces has instilled fear in villagers. The swift crackdown, coupled with ongoing surveillance from ranger patrols, has engendered a degree of discipline in some people. Rather than risking further repercussions, many villagers engage in 'everyday forms of resistance' through subtle acts of noncompliance to the conservation regulations. These practices are entangled with material benefits and moral statements about customary rights to resources. They may also facilitate political mobility by destabilizing conservation management, while simultaneously avoiding open confrontation with governing authorities. I refer to this overall process as the (un)making of marine park subjects.